PENGARUH PEMBIAYAAN MUDHARABAH BERDASARKAN PSAK NOMOR 105 TERHADAP LABA BERSIH DI BANK MUAMALAT INDONESIA PERIODE 2016-2020 - Putri, Melinia; Setiawan, Iwan; Wardiyah, Mia Lasmi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2022)
The purpose of this research is to find out the development of mudharabah financing at Bank Muamalat Indonesia for the 2016-2020 period; the development of net income at Bank Muamalat Indonesia for the 2016-2020 period; the suitability of the application of mudharabah financing accounting at Bank Muamalat Indonesia with PSAK Number 105; the effect of mudharabah financing on net income at Bank Muamalat Indonesia for the 2016-2020 period.This research uses a descriptive method with a quantitative approach. The data sources of this research are primary data obtained through interviews with the Branch Manager of Bank Muamalat KCP Ujung Berung, and secondary data in the form of financial statements for the 2016-2020 period published on the official website of Bank Muamalat Indonesia. And the data analysis used in this research is descriptive statistical analysis, simple linear regression analysis, correlation analysis, coefficient of determination analysis, and t test analysis. The results of the study show that 1) the development of mudharabah financing tends to decrease from the 2016-2020 period. 2) net profit for the period 2016-2020 tends to increase. 3) the accounting aplication of mudharabah financing at Bank Muamalat Indonesia is in accordance with PSAK Number 105. 4) Mudharabah financing has an effect net income with a value thitung ˂ ttabel yaitu -0,591 ˂ 2,101 and a significance value 0,562 ˃ 0,05. This means that H0 is accepted and H1 is rejected, then mudharabah financing has no effect on net income at Bank Muamalat Indonesia for the 2016-2020 period.